Pengelolaan Laboratorium Kimia Di Sma Negeri 2 Salatig - HARTATI, RATNI (2012)
The purpose of this study was to describe (1) Characteristics of the procurement of equipment and materials chemistry laboratory in Senior High School 2 Salatiga. (2) Characteristics of use of the chemical laboratory in Senior High School 2 Salatiga in chemistry learning. (3) Characteristics of the maintenance and repair of chemical laboratory in Senior High School 2 Salatiga. Form of this research is qualitative research, ethnographic design. In this study researchers took place in Senior High School 2 Salatiga is located at 79 Street Tegalrejo Salatiga. Data collection techniques using participant observation, interview or interviews, documentation. Analytical techniques used in this study is cross-site analysis. The results of this study were (1) Procurement of equipment and materials on chemical laboratorim an activity plan and hold a need for tools and materials chemistry laboratory by laboratory staff and assisted by the teacher of composition performed before the new school year, with the aim to prepare the implementation of learning in the new school year, as well as evaluating the implementation of learning in the previous year. Funding for procurement of laboratory equipment and materials are determined by the principal under a plan proposed by the teacher and selected by the procurement of goods and funds available. Procurement of goods damaged in the process of learning, will be held at the new school year, so this inhibits the use of chemical laboratory. (2) Chemical laboratory in Senior High School 2 Salatiga is used not only at intrakurikuler, but on the extra hours. Lobaratorium regulated through the use of scheduling. The use of chemical laboratory and do not have standard operating procedures (SOP) is fixed, so its use is determined by setting school policy. (3) Maintenance activities performed by each class with the current class schedule is completed using the laboratory and in a way the students to clean and store tools and materials the original place after using it and always ask for permission in advance to the teacher if you want to use the tools and materials in the lab and the teacher did supervision of the students in the use of tools and materials are currently being conducted laboratory practicum. Responsible for maintenance performed by a laboratory that is prepared by a special staff to supervise and mengkoordinator school laboratory. As for the improvements made in accordance with the type and the goods were damaged and handed over to a third party if the teacher can not do the repairs yourself.